Feeling good [compact disc] : her greatest hits and remixes - Simone, Nina, 1933-2003 (Verve, 2021)
The new album gathers the most iconic songs recorded throughout her career and includes seven remixes by some of the hottest, in-demand DJs worldwide. The first single from the set is a remix by English DJ/producer Joel Corry (Charli XCX, Ed Sheeran) of the timeless classic album. The album includes seminal songs such as Mississippi Goddam; Strange Fruit; I Loves You Porgy; I Put A Spell On You; Nina Simone's timeless version of Feeling Good.